ANTIMICROBIAL ASSAY OF MEDICINAL PLANT EXTRACTS AGAINST ORAL PATHOGENS - JESSE JOEL T; SREEJIT. N (International Journal of Pharma and Bio Sciences, 2016)
Oral diseases are a major health problem with dental caries and periodontitis featuring among the most infectious diseases and it is also a systemic disease. Various combinations of different plant extracts due to their inherent synergistic properties in the recent past have been used as potential antiplaque and anti-caries agents. Species of higher plants are much less surveyed for antibacterial activity. Application of antibiotics to eliminate the etiologic agents of these oral infections is not recommended because of the risk of the bacteria developing multi-drug resistance. This study is to check the antimicrobial activity of plant extracts against the bacteria isolated from the oral cavity of humans. The bacteria obtained from the oral cavity were found to be of two Bacillus spp. strains and 4 unknown isolates through identification and biochemical tests. The antimicrobial activity of the oral samples was studied by antimicrobial assay (well diffusion method) against the plant extracts prepared. Zones were observed and the maximum inhibition was found at 15mm and minimum inhibition was found at 6mm. The plant extracts showed a perceptible antimicrobial activity against oral samples.